Réponses

2014-04-13T10:40:36+02:00
Bonjour

A = (9x -7)² = 81x² - 126x + 49
B = (x+9)(11 -5x) = 11x - 5x² + 99 - 45x = -5x² - 34x +99
C = (2x-3)(2x+3) = 4x²  - 9
D = (11 +8x)² ) =  121 + 176x + 64x²
E = (x+1)² + 7x ( 2 -x) = x² +2x +1 + 14x - 7x² = -6x² +16x +1
F = (x+3)(2x-1) - 3x(2x+5) = 2x² -x +6x -3 - 6x² -15x = -4x² -10x -3
G = (4t +1)(4t -1) -(3t+2)² = 16t² -1 - (9t² + 12t +4) = 16t² -1 -9t² -12t -4 = 7t² -12t -5
H = 2(s+5)(s-5) +(4s +3)² = 2 (s² -25) + 16s² +24s +9 = 2s² - 50 + 16s² +24s +9
= 18s² +24x - 41
i = (3x+4)² - (1 -2x)(6+x) = 9x² +24x +16 - (6 +x -12x -2x²) = 9x² +24x +16 - 6 -x +12x +2x² = 11x² +35x +10

2014-04-13T10:44:00+02:00
A (9x-7)² = 81x² -126x +49  ( pour info (a-b)² = a²-2ab +b²)

b (x+9)(11-5x) = 11x -5x²+99-45x = -5x²-35x +99

c (2x-3)(2x+3) = 4x²+6x-6x +9= 4x²+9

d (11+8x)² =121+176x +64x²  ( pour info (a+b)² =a²+2ab+b²

e (x+1)² +7x(2-x) = x²+2x+1 +14x-7x² = -6x²+16x+1

f (x+3)(2x-1)-3x (2x+5) = 2x²-x+6x-3-6x²-15x = -4x² +5x -3

g (4t+1)(4t-1) -(3t-2)² =16t²-4t+4t-1 -(9t²-12t+4) =6t²-1-9t²+12t-4 = -3t²+12t-5

h 2(s+5)(s-5)+(4s+3)² =2(s²-5s+5s-25) +(16s²+24s+9) =2s²-50+16s² +24s+9
=18s²+24s-41

i(3x+4)²-(1-2x)(6+x) = 9x²+24x+16 -(6+x-12x-2x²) =9x²+24x+16 -6+11x+2x²
= 11x²+35x+10